Post-Truth, Democracy, and the Need for Critical Media Literacy - Walangarei, Angelita Sarina; Sitorus, Fitzerald Kennedy (CV. ITTC INDONESIA, 2023)
In an era of unprecedented information proliferation, post-truth dynamics, democratic principles, and critical media literacy are central for philosophical exploration. The rapid dissemination of information brings both opportunities and challenges to global democracies. The digital age has fundamentally altered how information is spread, intensifying competition for attention and accelerating information generation. Post-truth's influence, where emotions often overshadow facts in shaping public opinion, raises concerns about the very foundation of democracy. In this dilemma, mass media and journalism, crucial in shaping public opinion, sometimes prioritize attention-grabbing narratives over objective truth. Democracy, facing challenges in the age of limitless information, requires imparting critical media literacy skills to the populace. Media literacy involves not just technological understanding but also the ability to assess sources, understand context, and analyze motives.